Fossilization Understanding the Material Nature of Ancient Plants and Animals - Gee, Carole T. (Book collections on Project MUSE., 2021)
"This edited volume provides researchers with an in-depth look at cutting-edge innovations in the art and science of taphonomy--the branch of paleontology that deals with the processes of fossilization--bringing them up to date on current knowledge and defining future directions for research"--